Antibacterial effects of Thymus algeriensis extracts on some pathogenic bacteria - Messaoudi, Mohammed; Benreguieg, Mokhtar; Merah, Maroua; Messaoudi, Zakarya Ayoub (Acta Scientiarum. Biological Sciences, 2019)
Despite the presence of many antibiotics, bacterial resistance is growing steadily and some of these antibiotics have become ineffective, which poses a major challenge to the health sector. In this context, this work has demonstrated, in vitro, the inhibitory action of the bacterial growth resulting from methanolic and ethanolic extracts of Thymus algeriensis Boiss. & Reut., a medicinal plant species harvested from the Algerian South-west area, as well as the determination of the phenolic content of those crude extracts. The methanolic extract of Thymus algeriensis showed a significant antibacterial effect with 16.5 and 19 mm against Pseudomonas aeruginosa and Staphylococcus aureus, respectively. Klebsiella pneumoniae was not inhibited by both tested extracts. Besides, ethanol extract has not prevented the growth of the Enterobacter cloacae. This biological activity can be explained by the appreciable rates noted for both of the plant extracts in terms of total phenolic levels, which ranged between 79.45 and 67.13 mg GAE g-1 dry weight.